Development of a motherboard for CC1000 plug and play module - Ramos, Marlon M.; Arzadon, Alvin Joseph D. (2006)
Wireless sensor networks consist of sensor nodes communicating with each other in RF. Each node has its own transceiver, which transmits and receives information to and from the other nodes. Each node must be driven at low power sufficient enough for it to be easily managed. CC1000 is a flexible single chip very low power and very low voltage RF transceiver manufactured by Chipcon. It is suitable for use in the 868/915 MHz ISM (Industrial, Scientific, and Medical) frequency band. To serve as reference layout and quick prototyping of the CC1000 module, Chipcon designed a plug-and-play module for the CC1000 transceiver. This project aims to produce a motherboard that will allow students to closer investigate and explore the potential of wireless sensor networks. This motherboard will accommodate the CC1000 plug-and-play module and include an ATMEL Atmega128L microcontroller that will configure the CC1000 transceiver chip and also accommodate applications that will use the CC1000 for the physical layer of a wireless link. The motherboard will also include I/0 interface for the user of the board and pin-outs for the application of the board. The group designed a temperature sensor and interfaced it to the motherboard to demonstrate the wireless sensor network application of the motherboard. A point-to-point communication algorithm is developed for the temperature sensor application to help other researchers in developing algorithms for the motherboard. Part of the project is also dedicated to the characterization of the board's RF and baseband characteristics. The group also produced a user manual to aide the future users of the motherboard.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Wireless sensor networks; Plug and play (Computer architecture); Motherboards (Microcomputers); CC100 Plug and play module